SUATU PENDEKATAN ANALISIS MULTIVARIAT TENTANG TINGKAT KELAHIRAN PADA BEBERAPA KELOMPOK DAN ETNIS WANITA PERNAH KAWIN DI IRIAN JAYA - Pieter J. Soumokil (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1992)
It has been argued by many demographers that socio economic development with its associated fundamental changes in the role of women and the value of children is the dominant factor in the transition from high to low fertility. Research in less developed countries has found lower fertility levels in urban population compared to rural population. It was therefore assumed that the modernizing role of urbanlife helped bring about a decline infertility levels.This study in Irian Jaya, however, convincingly shows that fertility of urban women in Irian Jaya is higher than that of rural women. This differential infertility in favour of urban women in Irian Jaya appears to be real and not a result of underreporting of total live births in rural areas.The reasons for lower fertility in the rural areas in IrianJaya remain unknown, and more research is therefore needed. However, this study strongly suggests that the traditional system of swidden agricultyure in Irian Jaya, which places a highvalue on the labour input of women, may play a major role in constraining fertility in rural area of this province. On the other hand, high fertility in urban areas takes place because urbanwomen have their first birth earlier thanwomen inthe rural areas.